Antibiotics in Prevention and Treatment of Multi-Drug Resistant (MDR) Organisms causing Surgical Site Infection (SSI) - Saranya K. Lakshmi; Hema N. Gowda; Anuradha Kundapur (Pharmacology and Clinical Pharmacy Research, 2020)
Antibiotics play a vital role in prevention and treatment of various infections. But inappropriate antibiotic choice could lead to emergence of multi-drug resistance (MDR) among microorganisms. Since, the antibiotic susceptibility pattern of organisms could vary from place to place; forming a local prophylaxis and treatment protocol could hugely reduce this global burden. The primary objectives of the study were to observe the frequency of multi-drug resistant organisms causing Surgical Site Infections (SSIs) and to study the pattern of antibiotic usage for the prophylaxis and treatment of SSIs. A descriptive study was carried out in general surgical wards of KR hospital, Mysore for a period of 18 months (2015-2016). The relevant data was collected from the case sheets of patients who were diagnosed with SSI. Pus samples were collected, and culture-sensitivity was done. Collected data were analyzed using relevant statistical tests. A total of 263 study subjects including both males and females were enrolled in the study. Cefotaxime was the most common antibiotic used for pre-surgical prophylaxis (n=221). Out of 263 pus samples 92% were culture positive. The most common organisms causing SSI were E-coli-ESBL (n=73) and MRSA (n=44). About 95% of organisms showed multi-drug resistance. Imipenem, Gentamicin, Piperacillin-Tazobactum and Linezolid were the most common antibiotics used in the treatment of SSIs. The result of the study is alarming. Overall, there is great rise in the prevalence of MDR organisms causing SSIs. The hospital antibiotic policy should be revised in such a way to decrease the emergence of MDR microbes.